Meningkatkan Semangat dan Prestasi Lari Estafet: Implementasi Metode Jigsaw pada Siswa Kelas IX SMP Negeri 9 Sinjai - Husain, Andi Baso; Alif Tunru, Andi; Taufiq, Muhammad; Adianto, Samsul (SISTEMA: Jurnal Pendidikan, 2023)
This study aims to determine: the application of the jigsaw type of cooperative learning method can improve the learning outcomes of relay running in class IX students of SMP country 9 Sinjai. This research is action research conducted in the classroom, or classroom action research (Classroom Action Research) with two cycles. The research population was all students of class IX SMP Country 9 Sinjai, the sample in this study was one class consisting of 20 students. Data were collected through tests and observations. Data analysis used quantitative descriptive techniques. The results of the study in the first cycle showed that the percentage of student learning completeness was 60%, while in the second cycle the percentage of student learning mastery reached 85%. Thus, it was concluded that the application of the jigsaw type cooperative learning method could improve student learning outcomes in the relay running lesson